Low-cost hearing assistive technology development - Wong, Li Ying (2016)
The main objective of this project was to develop a low cost hearing assistive device. The device had to be able to split the input audio into various frequency spectrums which was similar to the frequency used in a hearing test. The gain of each frequency bandwidth was able to be controlled independently according to the user profile.